PENGARUH SHARIA COMPLIANCE DAN ISLAMIC CORPORATE GOVERNANCE TERHADAP KESEHATAN FINANSIAL PERBANKAN SYARIAH: Dibuat oleh Nur Hidayah, Djauhar Edi Purnomo, Rini Hidayah (Prodi Akuntansi FEB Universitas Muhammadiyah Pekajangan Pekalongan) - Rini Hidayah; Nur Hidayah; Djauhar Edi Purnomo (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2020)
The purpose of this study is to examine the effect of sharia compliance and Islamic corporate governance on the financial health of Islamic banking in 2013-2018. The population of this study is Sharia Banking that registered at Bank Indonesia (BI) and Otoritas Jasa Keuangan (OJK). The sample selection used the purposive sampling method, obtained 42 unit of analysis. The analized method used is multiple linier regression The result of this research indicate Islamic income and Islamic investment partially have a significant effect on the financial health of Islamic banking in the same period. Whereas profit sharing financing, zakat ratio, implementation of the duties and responsibilities of the sharia supervisory board, implementation of the duties and responsibilities of board directors, implementation of the internal audit functions and the application of an external audit functions have no significant effect on the financial health of the sharia banking in the 2013 to 2018 period. Keywords: Sharia Compliance, Islamic Corporate Governance, Financial Health, Sharia Banking.